Structure-property relations in regenerated cellulose fibers: comparison of fibers manufactured using viscose and lyocell processes - Sharma, Aakash; Nagarkar, Shailesh; Thakre, Shirish; Kumaraswamy, Guruswamy (Cellulose, 2019)
Regenerated cellulose fibers are produced using two industrially dominant technologies: the viscose and lyocell processes. Here, we compare commercially available fibers, prepared using the viscose and lyocell processes. Single fibers are subjected to a variety of mechanical deformations to obtain stress-strain, stress relaxation and stress recovery data. These are fitted to a phenomenological model, whose parameters are interpreted in terms of the fiber semicrystalline microstructure. This simple model does not incorporate the complexities of semicrystalline microstructure. Rather, it represents structure in a semicrystalline polymer fiber in terms of an elastic crystalline phase that coexists with a viscoelastic Voigt-like glassy amorphous phase. Lyocell fibers are characterized by higher values of crystalline modulus relative to viscose. Lyocell fibers also have a higher amorphous phase modulus and a wider relaxation spectrum than viscose, suggesting that amorphous and crystalline phases are dispersed in close connectivity in lyocell. Viscose and lyocell fibers exhibit qualitative similarities in their mechanical response. On stretching, there is a transition in the stress-strain curve from a low strain elastic response at a critical value of strain. This critical strain has been incorrectly attributed to yielding of the fiber. We establish that this critical value corresponds to an apparent yield. When subjected to strains higher than this apparent yield point, the fibers develop a memory of the mechanical deformation. This memory decays slowly, logarithmically with time and is lost over about a day as the fiber structure transitions back to the original as spun fiber. Finally, we demonstrate that on wetting the fibers with water, there is an increase in the apparent yield strain for viscose fibers, but not for lyocell. We interpret these results in terms of the semicrystalline microstructure of the fibers.
Keywords: mechanical properties; Model; Regenerated cellulose; Yielding

SANS and SAXS investigation of the melt state structure in disentangled ultrahigh molecular weight polyethylene - Sharma, Aakash; Kruteva, Margarita; Willner, Lutz; Romano, Dario; Porcar, Lionel; Dulle, Martin; Zhou, Fuhai; Rastogi, Sanjay; Richter, Dieter (ACS Macro Letters, 2025)
Disentangled ultrahigh molecular weight polyethylene exhibits a time-dependent increase in rheology modulus when molten. This originates from its kinetically evolving heterogeneous microstructure consisting of disentangled and entangled regions. We report a quantitative analysis of this microstructure using X-rays and neutrons that capture the signatures of these regions. We analyze the absolute intensities to obtain the volume fraction and size distribution of the disentangled domains in the melt. Employing neutrons, we follow the changes in these parameters with time. The trends are qualitatively similar to those of the previous rheological observations. Our methodology also provides an experimental verification of the theoretical report by McLeish, T. C. B. Soft Matter 2007, 3 (1), 83-87, which predicts the presence of high density disentangled domains in a low density entangled matrix. The analysis presented here is a useful instrument for unveiling the origin of differences in the properties of polymers obtained through different processing routes.

Simple two-step gelation process to strengthen 3D printed carboxy methyl cellulose gels - Rajput, Tejas; Sathe, Asmi; Gopal, Animesh; Sharma, Aakash; Shanmuganathan, Kadhiravan (Cellulose, 2026)
Carboxymethyl cellulose (CMC) is a water-soluble cellulose ether that is widely utilized in hydrogel applications due to its exceptional water absorption and biocompatibility. This study reports a simple two step strategy to make mechanically robust CMC gels without any additional chemical crosslinkers and how it could be leveraged to strengthen 3D printed CMC gels. These hydrogels, prepared through acid-induced gelation followed by freeze-thawing, exhibited a compressive modulus of 12.4 +/- 0.92 kPa and a compressive strength of 491.0 +/- 18.1 kPa. They could be leveraged for strengthening 3D printing hydrogels of intricate shapes by direct ink writing. Small amplitude oscillatory shear (SAOS) tests indicated an order of magnitude higher storage modulus for freeze-thawed gels (FC) as compared to only acid-induced CMC gels (HCMC). Nonetheless, stress relaxation experiments revealed that FC, as well as HCMC gels, relax at similar time scales. FC gels exhibited clear birefringence under crossed polarizers, indicating molecular ordering that is consistent with the presence of ordered/crystalline domains. Such ordered domains likely contribute to the higher elastic modulus and compressive strength observed in FC gels as compared to HCMC gels.
Keywords: 3D printing; Carboxymethyl cellulose; cellulose; Gels